HUBUNGAN LAMA MENDERITA DAN KOMPLIKASI DENGAN KUALITAS HIDUP WANITA PENDERITA DIABETES MELLITUS TIPE II DI RS MITRA MEDIKA TAHUN 2022 - Nila Sari (Lembaga Pengembangan Kinerja Dosen, 2022)
According to the World Health Organization (WHO) in 2010 reported that 60% of the causes of death of all ages in the world are due to Non-Communicable Diseases (NCDs). Diabetes Mellitus is ranked 6th as the cause of death. Data obtained at the Binjai Army Hospital suffering from type II diabetes mellitus in 2022 there were 430 cases. The purpose of the study is to determine the relationship between long suffering and complications with the Quality of Life of Women With Type II Diabetes Mellitus at binjai Army Hospital in 2022